Tumor associated macrophage × cancer cell hybrids may acquire cancer stem cell properties in breast cancer. - Jingxian Ding; Wei Jin; Canming Chen; Zhiming Shao; Jiong Wu (PLoS ONE, 2012)
Breast cancer is one of the most frequently diagnosed cancers among women, and metastasis makes it lethal. Tumor-associated macrophages (TAMs) that acquire an alternatively activated macrophage (M2) phenotype may promote metastasis. However, the underlying mechanisms are still elusive. Here, we examined how TAMs interact with breast cancer cells to promote metastasis. Immunohistochemistry was used to examine the expression of the M2-specific antigen CD163 in paraffin-embedded mammary carcinoma blocks to explore fusion events in breast cancer patients. U937 cells were used as a substitute for human monocytes, and these cells differentiated into M2 macrophages following phorbol 12-myristate 13-acetate (PMA) and M-CSF stimulation. M2 macrophages and the breast cancer cell lines MCF-7 and MDA-MB-231 fused in the presence of 50% polyethylene glycol. Hybrids were isolated by fluorescence-activated cell sorting, and the relevant cell biological properties were compared with their parental counterparts. Breast cancer stem cell (BCSC)-related markers were quantified by immunofluorescence staining, RT-PCR, quantitative RT-PCR and/or western blotting. The tumor-initiating and metastatic capacities of the hybrids and their parental counterparts were assessed in NOD/SCID mice. We found that the CD163 expression rate in breast cancer tissues varied significantly and correlated with estrogen receptor status (p<0.05). The fusion efficiency of either breast cancer cell line with M2 macrophages ranged from 1.81 to 6.47% in the presence of PEG, and no significant difference was observed between the breast cancer cell lines used (p>0.05). Characterization of the fusion hybrids revealed a more aggressive phenotype, including increased migration, invasion and tumorigenicity, but reduced proliferative ability, compared with the parental lines. The hybrids also gained a CD44(+)CD24(-/low) phenotype and over-expressed epithelial-mesenchymal transition-associated genes. These results indicate that TAMs may promote breast cancer metastasis through cell fusion, and the hybrids may gain a BCSC phenotype.